"Puxo o cavaquinho pra cantar de galo" : conflito e solidariedade no circuito do choro de Aracaju - Bezerra, Daniela Moura (2011)
We propose to study in a general way the presence of the musical gender choro (Brazilian musical gender) in the city Aracaju, in Sergipe, Brazil. It inquire which principles give legitimacy to the groups of choro existing in Sergipe s capital, and how the search for legitimacy influences the social relations constructed inside of what we denominated Aracaju s circuit of choro. This term is used as a reference to a common expression among the groups of choro of this city. It is also used as an analyses category which describes the ways of use of an urban space which give support to one determined practice and a observable existence. This circuit is composed by seven choro group that are distributed in distinguished neighborhoods of the city. The concept defended in this dissertation is that Aracaju s choro circuit is fragmented and disputed by the different groups that are part of it, in the search of prestige positions to be occupied by them. These disputes generate the establishment of rivalries which mainly occur between the older and the younger groups, and the construction of solidarity nets as a strategy of being insert on choro context in Sergipe. This paper is structured in three chapters. The first chapter proposes to present the existing representations about this gender and how it has been used as a justification to elaborate projects that incentives its practice and as a motive to explain the option of playing it. In the second chapter is presented the circuit and the relations established in its inner, it is, the practices of solidarity and rivalry. The last chapter analyzes the principles activated to the legitimization of choro groups and the identity rhetoric of being chorão (the musician that plays choro) in Aracaju.